2017
DOI: 10.1001/jamaoto.2016.3802
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Performance of a New Staging Category to Improve Discrimination of Disease-Specific Survival in Nonmetastatic Oral Cancer

Abstract: In this study, new staging category had better DSS discriminatory ability and could help to identify high-risk patients for intense adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…That Tsai obtained non‐significant results when the cutoff for NLR was set at 5 suggests the optimal cutoff value should <5 for oral cancers. Interestingly, a significant association was observed between NLR and TNM stage in oral cancers . In our study, however, most cases were not advanced stage cancers, which may also explain why the optimal cutoff for NLR varied.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…That Tsai obtained non‐significant results when the cutoff for NLR was set at 5 suggests the optimal cutoff value should <5 for oral cancers. Interestingly, a significant association was observed between NLR and TNM stage in oral cancers . In our study, however, most cases were not advanced stage cancers, which may also explain why the optimal cutoff for NLR varied.…”
Section: Discussioncontrasting
confidence: 55%
“…At present, the prognosis and treatment of OSCC are based mainly on the American Joint Committee on Cancer (AJCC) TNM classification which was based on tumor's size, spread to lymph nodes and metastasis . However, a major limitation of this classification is that it is not perfectly accurate, and a combination of other factors is more predictive of prognosis than traditional tumor staging in patients with OSCC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel prognostic systems have been developed incorporating NLR, such as the combination of NLR and platelet counts in hypopharyngeal cancer, or histopathological staging and NLR in oral cancer . Other inflammatory markers and systems, such as the platelet‐to‐lymphocyte ratio, lymphocyte‐to‐monocyte ratio, and Glasgow Prognostic Score have also received interest as prognostic indicators in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%